Seducción y (hetero)erotismo en perspectiva: reiteración, desplazamientos e incorporaciones de sexo/género/deseo performativamente materializadas. - Bianciotti, María Celeste (Revista Pensamiento Americano)
Considering the formative character of erotic performances and sex/gender/desire on the subjectivities, this paper proposes to demonstrate certain aesthetic/erotic/corporal ways of seduction and eroticism through which a corpus of young women (re)produced processes of self-constitution. This article deduces from an ethnography which empiric object represented seduction performances and (hetero)erotic interactions of a corpus of thirty young women studying at university that lived in the city of Córdoba, Argentina, between 2009 and 2012.